Evaluating the Analytic - Continental Divide: Impact on Education in Croatia - Novak, Ivona (Journal of Education Culture and Society, 2020)
Contemporary Western philosophy has been generally perceived as one that encompasses two divergent traditions of philosophical thought: analytic and continental. A number of writers have drawn attention to the difficulty of explaining the differences between them. A small number of authors have even questioned the credibility of the analytic-continental division. In this paper I argue that the gulf between traditions is real and has a negative impact on three elements of education in Croatia: philosophy as an academic subject, students and university professors. Before delving into the aforementioned issue, I briefly specify areas of philosophical inquiry where the gulf is the most evident. I end paper with several suppositions concerning the future path of both traditions, which are mostly based on the idea of cooperation between analytic and continental philosophers as it would profoundly contribute to the advancement of teaching philosophy.